(untitled) (Jurnal Agribisnis dan Agrowisata, 2026)
Contribution of Inul Watermelon Farming to Farmers’ Income in West Intaran, Sanur Kauh Village, Denpasar City. Inul watermelon in Indonesia is very popular and consumed by many families because it has a smaller size which is suitable for families and a sweeter taste. One of the commodities cultivated by farmers for the last five years in Sanur Kauh Village, Denpasar City. This research aims to determine the income of farmers in Subak Intaran Barat and to find out how much contribution Inul watermelon has to the income of farmers in Subak Intaran Barat. The methods used in this research are quantitative and qualitative methods. Data collection will be carried out from October 2023 to November 2023 in Subak Intaran Barat, Sanur Kauh Village, Denpasar City. The results of this research show that the source of income for Inul watermelon farmers is IDR146.121.931/year with an average cultivated area of 0.54 Ha and a contribution of 39% of the farmers’ total income of IDR 379.159.957/year. The obstacles faced by farmers in sweet corn farming in Subak Intaran Barat consist of technical obstacles, namely pests, disease and climate, as well as non-technical obstacles, namely the use of information technology. Suggestions that need to be considered are that members in Subak Intaran Barat should maintain their Inul watermelon farming business and develop their Inul watermelon farming business by utilizing technology in their Inul watermelon farming business to be able to compete with other products and improve the quality of farming.